2021
DOI: 10.4018/ijssmet.2021110108
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment and Its Impact on Job Performance

Abstract: This study aimed to identify the availability level of organizational commitment (OC) among employees in the Jordanian commercial banks, as well as to measure its impact on their job performance (JP). To achieve the objective of the study, 257 copies of the questionnaire were distributed to a random sample of employees at all administrative levels in the Jordanian commercial banks. The results of the study have indicated that OC is available in Jordanian banks with a high degree. Moreover, it has showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Many similar studies rank the "management commitment" as the top leading factor in safety climate, however, the results of this study rank the "management commitment" as the third important factor that highly influence the safety climate in Oman (Zohar, 1980;Dedobbeleer and Beland, 1991; HSE (UK), (1997); Neal et al, 2000;Seo et al 2004;Pousette et al 2008;Kines, et al, 2011;CPWR, 2017). Organizational and management commitment was also considered important by Al-Tarawneh (2021) as it has a significant impact of job performance. Such commitment also provides better environments that produce highly motivated employees to attain organizational goals (Galli, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many similar studies rank the "management commitment" as the top leading factor in safety climate, however, the results of this study rank the "management commitment" as the third important factor that highly influence the safety climate in Oman (Zohar, 1980;Dedobbeleer and Beland, 1991; HSE (UK), (1997); Neal et al, 2000;Seo et al 2004;Pousette et al 2008;Kines, et al, 2011;CPWR, 2017). Organizational and management commitment was also considered important by Al-Tarawneh (2021) as it has a significant impact of job performance. Such commitment also provides better environments that produce highly motivated employees to attain organizational goals (Galli, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Performance evaluation is also defined as providing a judgment about the employee's capabilities and the extent of their willingness to the development, in order to ensure their ability to implement job responsibilities and to verify the nature of their behavior and actions in the work environment as, as well as to identify weaknesses, strengths, and training needs (Denisi & Murphy, 2017). Al-Tarawneh (2021) aimed to identify the effect of HRM practices on organizational commitment of the workers in the Jordanian pharmaceutical sector; their results showed that HRMS (performance evaluation in particular) have a positive effect on organizational commitment and improve job performance, which is positively reflected on strategic success. Moreover, many studies have shown that adopting an effective performance evaluation strategy plays an important role in improving and developing the capabilities of individuals, which will positively affect the achievement of the organization's goals and the implementation of the strategic plan (Elbanna et al, 2016;Salamzadeh et al, 2018;Zehir et al, 2016).…”
Section: Performance Evaluation Strategymentioning
confidence: 99%